Material didáctico en el área de matemáticas y su incidencia en el aprendizaje de los niños y niñas del cuarto año de educación general básica - Viera Molina, Clara Guadalupe (2017)
The purpose of the research was to determine the use of educational material affects in the teaching - learning of Mathematics subject; the objective was to: Establish the impact of the use of educational materials in the learning of mathematics subject of the children from fourth year of Basic Education at "Carlos Freile Larrea" School through collecting valid information for the consolidation of specific skills. It is necessary to specify that the study was carried out in the El Murco Community from Tambillo Parish, Mejía canton, located in the Pichincha Province. The type of research used is quantitative, it worked with statistical data collected with applied surveys, also it corresponds to the type of descriptive research and it was determined important characteristics of the didactic resources and their effects in the learning; In addition, it used the techniques of the survey and the interview with their corresponding instruments of data collection….